Pembelajaran Band di Kelas XI Musik SMK Negeri 7 Padang - M. Rizki; Tulus Handra Kadir (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The purpose of this study is to describe the implementation of band learning in class XI of SMK Negeri 7 Padang. This type of research is a quantitative research with a descriptive analysis method. The research instrument is the researcher himself and is assisted by supporting instruments in the form of documentation and diary. Data was collected through literature studies, observations, interviews, and documentation. The steps of analyzing the data are data reduction and conclusions/withdrawal/verification. The results of the study show that the band learning process in Class XI Music SMK Negeri 7 Padang consists of planning, implementation and evaluation. Planning using lesson plans that are in accordance with the curriculum used by schools. The implementation refers to the RPP by showing videos about several songs from the rock music genre. The evaluation was carried out after the teacher's performance (exam) gave group and individual scores, but the performance was not satisfactory because the teacher did not fully accompany during the exercise. Based on the results of research that has been conducted as many as 4 meetings that band learning in class XI music SMK N 7 Padang does not run smoothly due to the lack of seriousness of students in learning, this can be seen from students only relying on lesson time as their learning and practice time, and there is a difference between lesson plans and learning in the classroom, and there are also other factors such as the limitation of instruments and music studios for students to practice with groups.